Cosmogenic Exposure Dating (36Cl) of Landforms on Jan Mayen, North Atlantic, and the Effects of Bedrock Formation Age Assumptions on 36Cl Ages - Johanna Anjar; Naki Akҫar; Eiliv A. Larsen; Astrid Lyså; Shasta Marrero; Nasim Mozafari; Christof Vockenhuber (Geosciences, 2021)
Jan Mayen is a small volcanic island situated 550 km north of Iceland. Glacial sediments and landforms are relatively common on the island but, so far, only a few of them have been dated. In this study, we present and discuss 89 36Cl dates of primarily glacial and volcanic events on Jan Mayen. Calculations of sample exposure ages were complicated by young exposure ages, young rock formation age, and high native Cl contents, leading to updates in CRONUScalc to enable accurate exposure age calculations. The samples provide good evidence against an equilibrium assumption when subtracting background production (e.g., 36Cl produced by neutron capture from fission of U or Th) for samples on young bedrock, with younger exposure ages most significantly affected. Exposure ages were calculated with a range of assumptions of bedrock formation ages appropriate for Jan Mayen, including the assumption that the rock formation age equaled the exposure age (i.e., the youngest age it could possibly have), and we found that although the effect on most of the ages was small, the calculated ages of 25 of the samples increased by more than 1 standard deviation from the age calculated assuming equilibrium background production, with a maximum deviation of 6.1 ka. Due to the very young bedrock on Jan Mayen, we consider the nonequilibrium ages to be the most reliable ages from the island and conclude that large-scale deglaciation on the south and central, lower-lying, parts of the island, started around 20 ka and lasted until ~7 ka. On northern Jan Mayen, the slopes of the 2277 m high stratovolcano Beerenberg are currently partly glaciated; however, outside of the Little Ice Age moraines, all but two samples give ages between 14 and 5.7 ka.